Avian paramyxovirus 4 isolated from the mallard (Anas platyrhynchos, Linnaeus, 1758): the first case detected in the Western Caspian region - A. A. Derko; N. A. Dubovitskiy; T. A. Murashkina; I. A. Sobolev; M. V. Solomatina; A. Yu. Alekseev; M. G. Magomedov; J. Mine; Yu. Uchida; T. Saito; M. M. Kallaeva; K. A. Sharshov (Юг России: экология, развитие)
Aim. The work is aimed at exploring the molecular and genetic properties of avian paramyxovirus 4 (APMV‐4) isolated from the mallard duck. Material and Methods. In 2018, as a part of an influenza A virus surveillance programme, biological samples were collected from wild birds on Lake Adzhi (Papas) in the Republic of Dagestan. The isolation of virus strains from biological samples was performed using 10‐day‐old special pathogen‐free chicken eggs. The primary detection of hemagglutinating agents in the fluid of the allantoic cavity was carried out via hemagglutination assay. The presence of RNA of the influenza A virus was determined using Real Time PCR. Then, for samples negative in PCR for the influenza A virus, the complete genome DNA sequences were established using NGS sequencing. It was determined that the APMV‐4 strain obtained belonged to intraspecific genetic lines was determined using phylogenetic analysis.Results. APMV‐4 strain was isolated for the first time in the Western Caspian region. Phylogenetic analysis of the complete genome and gene F showed that the APMV‐4/mallard/Dagestan/92d/2018 strain belongs to the Eurasian clade of subgenotypes. Analysis of amino acid substitutions showed that the cleavage site of the fusion protein is monobasic which is characteristic of lentogenic strains.Conclusion. During the surveillance program for influenza A viruses in autumn 2018, the APMV‐4 strain was isolated from the mallard duck. Analysis revealed that the APMV‐4 strain was closely phylogenetically related to strains isolated from two wild and one domestic duck from China. This suggests an interconnection between the bird populations in China and the Western Caspian region within the West Asian‐East African migration route.